2022
DOI: 10.3389/fpubh.2022.966461
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific associations between environmental factors and epistaxis

Abstract: ObjectiveSeveral studies have demonstrated that environmental factors, such as meteorological factors and air pollutants, are closely associated with epistaxis. However, age-specific associations between environmental factors and epistaxis have not yet been evaluated. This study aimed to evaluate the associations between individual meteorological factors and air pollutants and epistaxis, by age.Study designA retrospective cohort study.SettingRecords of patients covered by the Korean National Health Insurance S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Traditionally, the incidence of spontaneous epistaxis has been thought to be negatively correlated with ambient temperature, which has been demonstrated and repeated in many settings including the United Kingdom (U.K.), Korea, and Italy. 2,[4][5][6][7] One recent study examining internet search engine queries in major cities in the U.S. found that epistaxis search activity was inversely correlated with temperature, with this trend being strongest in cities with the greatest seasonal variations in temperature such as New York, Philadelphia, and Atlanta. 8 Interestingly, even amongst studies that have demonstrated a negative relationship between temperature and incidence of epistaxis, there have been substantial variations in the effect size of this correlation.…”
Section: Effect Of Temperature On Epistaxismentioning
confidence: 99%
See 4 more Smart Citations
“…Traditionally, the incidence of spontaneous epistaxis has been thought to be negatively correlated with ambient temperature, which has been demonstrated and repeated in many settings including the United Kingdom (U.K.), Korea, and Italy. 2,[4][5][6][7] One recent study examining internet search engine queries in major cities in the U.S. found that epistaxis search activity was inversely correlated with temperature, with this trend being strongest in cities with the greatest seasonal variations in temperature such as New York, Philadelphia, and Atlanta. 8 Interestingly, even amongst studies that have demonstrated a negative relationship between temperature and incidence of epistaxis, there have been substantial variations in the effect size of this correlation.…”
Section: Effect Of Temperature On Epistaxismentioning
confidence: 99%
“…Similar to prior studies, we found inverse associations between humidity and epistaxis incidence. 2,5,7,23 Under the IECC climate zone classification system, moist and dry humidity subclassifications were given for temperature zones 1-6. We found statistically significant increases in epistaxis rates in dry climate zones compared to moist climate zones for temperature zones 3-6, but interestingly not for temperature zones 1-2.…”
Section: Effect Of Humidity On Epistaxismentioning
confidence: 99%
See 3 more Smart Citations